Inequality, Poverty and Social Welfare in Greece: Distributional Eﬀects of Austerity - Mitrakos, Teodore M. (Études helléniques / Hellenic Studies, 2014)
Tis paper presents the recent trends and the characteristics of inequality, poverty and living conditions in Greece, emphasising the distributional eﬀects of the austerity measures adopted during the current economic crisis. Moreover, the decomposition analysis of the study examines the structure of inequality and the contribution of various income sources in overall inequality, while the main characteristics of the Greek social solidarity system and the poor distributional impact of social benefts are also discussed. To this end, household income from the Greek Household Budget and the EU Statistics of Income and Living Conditions surveys are used. The available data indicate that income inequality and relative poverty has increased, yet not dramatically, during the current crisis, although the composition of the poor population changed considerably. However, the sharp decline in disposable income and the dramatic increase in unemployment has led to a signifcant deterioration in economic prosperity and absolute poverty, i.e. when the poverty line in real terms remains stable in the pro-crisis levels.